2006
DOI: 10.1002/pi.2013
|View full text |Cite
|
Sign up to set email alerts
|

Extremely regio‐regular poly (3‐alkylthiophene)s from simplified chain‐growth Grignard metathesis polymerisations and the modification of their chain‐ends

Abstract: A simplified route to regio-regular poly(3-alkylthiophene)s (P3AT) with predetermined molecular weights and low molecular weight distributions based on the chain-growth GRIM polymerisation of 2,5-dibromo-3alkylthiophenes is detailed. It is proposed by way of in-depth 13 C-, 1 H-and two-dimensional NMR characterisations that the resulting P3ATs are quasi-100% regio-regular except for one regio-irregular pair at one chain-end. It is probable that chain-end groups exhibit reduced conjugation with the rest of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 56 publications
2
35
1
Order By: Relevance
“…[26] Characterization of P3HT-1 using 1 H and 13 C NMR spectroscopy suggested that the integrals of the main-chain and chain-end hydrogens give a good indication of the molecular weight, provided that it is not too high. [25] Using this technique, a coefficient of 1.6 was determined for P3HT-1. Dividing 4500 by 1.6 gives M n = 2800 g mol -1 (equivalent to around 17 units), which is in close agreement with that predicted.…”
Section: Molecular Weight Distributions Regioregularities and Purifmentioning
confidence: 99%
See 4 more Smart Citations
“…[26] Characterization of P3HT-1 using 1 H and 13 C NMR spectroscopy suggested that the integrals of the main-chain and chain-end hydrogens give a good indication of the molecular weight, provided that it is not too high. [25] Using this technique, a coefficient of 1.6 was determined for P3HT-1. Dividing 4500 by 1.6 gives M n = 2800 g mol -1 (equivalent to around 17 units), which is in close agreement with that predicted.…”
Section: Molecular Weight Distributions Regioregularities and Purifmentioning
confidence: 99%
“…In addition, P3BT was not reactive enough to be debrominated by metathesis. [25] P3HT-6 was expected to have a molecular weight of around 40 000 g mol -1 but was indicated by GPC to have M n = 33 400 g mol -1 , which equates to a 'realistic' molecular weight of 33 400/2 ≈ 17 000 g mol -1 . P3HT-7, prepared in diphenyl ether (DPE), was not subject to treatment with LiAlH 4 as it had a very low concentration of chain ends.…”
Section: Molecular Weight Distributions Regioregularities and Purifmentioning
confidence: 99%
See 3 more Smart Citations